Polyimide Electrode-Based Electrical Stimulation Impedes Early Stage Muscle Graft Regeneration - Srinivasan, Shriya; Vyas, Keval; McAvoy, Malia; Calvaresi, Peter; Khan, Omar F.; Langer, Robert; Anderson, Daniel G.; Herr, Hugh (Frontiers in Neurology, 2019)
Given the increasing use of regenerative free muscle flaps for various reconstructive procedures and neuroprosthetic applications, there is great interest and value in their enhanced regeneration, revascularization and reinnervation for improved functional recovery. Here, we implant polyimide-based mircroelectrodes on free flap grafts and perform electrical stimulation for six weeks in a murine model. Using electrophysiological and histological assessments, we compare outcomes of stimulated grafts with unstimulated control grafts. We find delayed reinnervation and abnormal electromyographic (EMG) signals, with significantly more polyphasia, lower compound muscle action potentials and higher fatigability in stimulated animals. These metrics are suggestive of myopathy in the free flap grafts stimulated with the electrode. Additionally, active inflammatory processes and partial necrosis are observed in grafts stimulated with the implanted electrode. The results suggest that under this treatment protocol, implanted epimysial electrodes and electrical stimulation to deinnervated and devascularized flaps during the early recovery phase may be detrimental to regeneration. Future work should determine the optimal implantation and stimulation window for accelerating free muscle graft regeneration.